2022
DOI: 10.1007/s11739-022-03037-2
|View full text |Cite
|
Sign up to set email alerts
|

Ergogenic value of oxygen supplementation in chronic obstructive pulmonary disease

Abstract: Patients with COPD exhibit limited exercise endurance time compared to healthy age-matched individuals. Oxygen supplementation is often applied to improve endurance time during pulmonary rehabilitation in patients with COPD and thus a comprehensive understanding of the mechanisms leading to improved endurance is desirable. This review analyses data from two studies by our research group investigating the effect of oxygen supplementation on cerebrovascular, systemic, respiratory and locomotor muscle oxygen avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…A possible explanation for the improvements with hyperoxia could be a change of energy metabolism while breathing supplemental oxygen, shifting the anaerobic threshold to more sustained aerobic metabolism with longer aerobic steady-state periods in CWRET [ 3 ]. We found significantly reduced levels of blood lactate in CWRET at end-exercise which are in line with another study that observed similar findings at end-exercise and isotimes in patients with COPD [ 24 ]. The higher blood oxygenation at end-exercise ( S pO 2 : IET +4%, CWRET +6%; S aO 2 : IET +7%, CWRET +9.6%) could additionally lead to an inhibition of hypoxia-stimulated chemoreceptors which decrease V ′ E and HR, resulting in more efficient breathing patterns.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A possible explanation for the improvements with hyperoxia could be a change of energy metabolism while breathing supplemental oxygen, shifting the anaerobic threshold to more sustained aerobic metabolism with longer aerobic steady-state periods in CWRET [ 3 ]. We found significantly reduced levels of blood lactate in CWRET at end-exercise which are in line with another study that observed similar findings at end-exercise and isotimes in patients with COPD [ 24 ]. The higher blood oxygenation at end-exercise ( S pO 2 : IET +4%, CWRET +6%; S aO 2 : IET +7%, CWRET +9.6%) could additionally lead to an inhibition of hypoxia-stimulated chemoreceptors which decrease V ′ E and HR, resulting in more efficient breathing patterns.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, a recent review [24] reported the physiological mechanisms underlying the beneficial ergogenic effect of FiO 2 1.0 compared to ambient air on CWRET at the endexercise and at isotime in patients with COPD. Authors synthesised data from two different trials undertaken by their group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Oxygen supplements reduce ventilatory requirements and hence dynamic hyperinflation during exercise in patients with COPD – even in patients that maintain saturation during exercise [ 53 ]. In patients with more pronounced desaturation during exercise [ 54 , 55 ], but not those with mild hypoxia [ 56 ], oxygen supplements also lead to reduced lactate levels during exercise. Hence both chemoreceptor inhibition as well as lower lactate may cause lower ventilatory needs during exercise in patients with COPD.…”
Section: Reversing Physiological Problemsmentioning
confidence: 99%